SEKSUALITAS PEREMPUAN DALAM BUDAYA PATRIARKHI - Danik Fujiati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
This paper examines the culture of patriarchy, which dominate and discriminate against women. Control of patriarchy on female sexuality, making them no longer have authority over his own body. Culture that built into the foundations of a patriarchal society with control over female sexuality, be threatening the existence of women was regarded as liyan, so that it becomes the root of the problem of gender inequality. Contributions patriarchy over the control of women's sexuality, make women experiencing the condition in which, when there are any problem affecting the female body (biological), then it happens because women's own fault. Ironically, in a society characterized by patriarkhisme, then the control, domination and discrimination both in the public and domestic over women's bodies become considered reasonable by the community, even countries.